Outcome of kangaroo mother care in terms of hospital stay among preterm infants in a tertiary health care center Bhuj, Kutch: a cross-sectional study - Patel, Jaivik Sureshbhai; Solanki, Gopi Alabhai (International Journal of Contemporary Pediatrics, 2021)
Background: Neonates born before 37 completed weeks of pregnancy are called premature infants. The birth of premature infants is associated with several problems, such as frequent hospital admissions, infections, apnea and others. Evidence suggests that kangaroo mother care is effective and safe alternative to conventional neonatal care, especially in under-resourced settings and may reduce morbidity and mortality in low birth weight infants as well as increase breastfeeding. Methods: Present observational study conducted in the department of pediatrics, Gujarat Adani Institute of Medical Sciences, Bhuj, Kutch, Gujarat for the Duration of 1 year. Source of data are all live new born of gestational age of less than 37 weeks and birth weight below 2500 gm delivered at GAIMS, Bhuj. Primary outcome measures were: rate of infection time frame 1-2 weeks (during hospital stay), frequency of presume sepsis and need for antibiotics, length of stay (time frame 1-2 weeks) and total days in hospital during recruitment period. Results: An average length of hospital stay was 15.31±12.01 days among neonates in our study group. Among those with infection duration of stay was 21.03±15.627 days and among those without infection were 12.09±10.402 days. There was significant difference in length of hospital stay among those with infection and without infection. Conclusions: Kangaroo mother care improves physiological indices in normal levels, thus it might positively influence the premature infant’s physical health. The present study has important implications in the care of preterm and LBW infants in the developing countries, where expensive facilities for conventional care may not be available at all places.